Comparison of compressive strength of recycled type III gypsum and Portland Composite Cement mixtures with manufactured type III gypsum: Perbandingan kekuatan tekan campuran gipsum tipe III daur ulang dan Portland Composite Cement dengan gipsum tipe III pabrikan - Anisa Permata Ermiyon; Aria Fransiska; Nelvi Yohana (Makassar Dental Journal PDGI Makassar, 2024)
The study was conducted to compare the compressive strength of recycled type III gypsum and Portland Composite Cement (PCC) mixtures with manufactured type III gypsum in a laboratory experiment with post-test only control group design. A total of 20 samples were divided into 5 gypsum groups, namely type III manufactured, type III recycled, a mixture of type III recycled and PCC at 1%, 3%, and 5% respectively. The compressive strength test was conducted using Universal Testing Machine and ana-lysed using one-way Anova test. The highest compressive strength was obtained for the manufactured type III gypsum and the lowest compressive strength was obtained for the recycled type III gypsum; there was a significant difference in compressive strength (p<0.05) between the treatment groups. It was concluded that the addition of various concentrations of PCC to recycled type III gypsum increased the compressive strength of recycled type III gypsum, although it did not match that of manufactured type III gypsum.